Exploring Relationships between Destination Brand Equity, Satisfaction, and Destination Loyalty: A Case Study of Mongolia / Odonchimeg Myagmarsuren and Ching-Fu Chen - Myagmarsuren, Odonchimeg; Chen, Ching-Fu (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
There has been growing interest among researchers in knowing the concept of the customer-based brand equity (CBBE) model which is widely applied in marketing research. In this study, the researchers made an attempt to apply the concept of customer-based brand equity as a tourism destination (CBBETD) by incorporating various antecedents of destination brand equity that leads to tourist satisfaction and destination loyalty. A conceptual relationship model is proposed and examined by using Mongolia as a tourism destination. The study concluded that tourists' awareness of a tourism destination which influences a positive perception of the image can lead to the expectation and actual experience of perceived service quality. Moreover, tourists want to become satisfied with the perceived tourism quality, and subsequently with aspects that influence loyalty.